Analysis of Students’ Mathematical Thinking Ability in Terms of Self Efficacy (Unnes Journal of Mathematics Education, 2022)
Mathematical thinking ability must be owned by students to solve various problems. Students are considered capable of fulfilling the indicators of mathematical thinking ability properly if they are balanced with good self-efficacy abilities. This research method is qualitative which aims to find new indicators and describe mathematical thinking ability in terms of self-efficacy and provide recommendations for teachers. The research subjects were six students from the first year of senior high school using purposive sampling. Indicators of mathematical thinking ability, include 1) Reasoning: identifying concepts and problems; 2) Generalizing: demonstrating mathematical ideas in writing and using mathematical language to express ideas correctly; 3) Critical Thinking: using representations to create mathematical models; 4) Problem Solving: planning problem solving strategies, implementing and checking results. 5) Communicating: revealing the results of problem solving. The results: 1) low self-efficacy’s students were only able to master reasoning; 2) moderate self-efficacy’s students are able to master reasoning, generalizing, and critical thinking; 3) high self-efficacy’s students are able to master all indicators. Recommendations for teachers are by giving opportunity to low self-efficacy’s students to speak in public, give appreciation for their efforts and reprimand if it doesn’t lower their confidence when they make mistakes.